Digital Literacy in Primary School: A Systematic Review of Let’s Read Implementation (2019-2025) - Arman Surya Wibowo; Nuni Widiarti; Arif Widiyatmoko (Papanda Publisher, 2026)
This study aims to map research trends, methodological tendencies, and scholarly contributions related to literacy learning through the Let’s Read application in primary schools during the period 2019–2025. This review is motivated by the growing demand for effective digital literacy media to address low reading interest and limited text comprehension among elementary students. Employing a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 protocol, the study followed four stages: identification, screening, eligibility assessment, and thematic synthesis. Data were collected from multiple academic databases, including Google Scholar, Garuda, SINTA, DOAJ, ResearchGate, and ScienceDirect, resulting in 32 relevant articles that met the inclusion criteria. The findings reveal a clear shift in research trends from an initial focus on basic literacy skills toward the integration of multimodal features, motivational strategies, and affective dimensions in digital literacy learning. Methodologically, the reviewed studies were dominated by qualitative and experimental designs, with an increasing use of mixed-methods approaches in recent years. Substantively, the majority of studies reported positive effects of Let’s Read on students’ reading interest, comprehension, and engagement, supported by its interactive, visual, and narrative elements. This review fills the gap of a systematic synthesis focusing specifically on Let’s Read as a digital literacy tool in primary education and highlights the need for longitudinal studies, stronger family involvement, and cross-cultural investigations to optimize its implementation and impact.